Effect of age, daily rhythm and mating on pheromone titres and trapping of Glyphodes pyloalis (Lepidoptera, Crambidae). (24th March 2022) - Guo, Qianshuang; Yang, Songjie; Zhuo, Fuyan; Xiang, Wenli; Feng, Chuanhong; Zhang, Suli; Du, Yongjun
Abstract: Glyphodes pyloalis (Lepidoptera, Crambidae) is an important pest of mulberry trees in China, and current methods for accurate population monitoring and control of this pest are lacking. The sex pheromone of G .  pyloalis in China was re‐identified as E 10, E 12, Z 14‐hexadecenyl acetate (E10E12Z14‐16:Ac) and tentatively E 10, E 12, E 14‐hexadecenyl acetate (E10E12E14‐16:Ac). The emergence began 2 h before the dark period, and the peak emergence was 3 h into scotophase. Analysing the female moth's age from 1–9 days revealed that the titre of sex pheromone E10E12Z14‐16:Ac and E10E12E14‐16:Ac did not change statistically, and the ratio remained constant at 7.19 ± 1.12. The titre of pheromone had a significant circadian rhythm, increasing at 2 h after darkness, peaking at 6–8 h before decreasing, but it was still detected after 4 h into photophase. Mating of G .  pyloalis occurred mainly at night, with the highest rate during 3 h into scotophase, which was earlier than the temporal pattern of pheromone titres. 18.1% of unfed moths mated immediately after eclosion during the scotophase. This was lower than what is seen in 1–3‐day‐old moths but similar to 4‐day‐old moth. Mating can occur on the same day after emergence, primarily within 1–4 days. Female moths can release pheromone again 48 h after mating, but the ratio of E10E12Z14‐16:Ac and E10E12E14‐16:Ac was reduced to 5.1 ± 0.73. The trapping of male moths in the field showed a significant circadian rhythm, but significant differences in pheromone trapping in Sichuan Gongxian, Zhejiang Chun'an and Haining, and Jiangsu Wujiang were observed. At the same location, the circadian rhythm of moth trapping showed differences between generations. The trapping of the overwintering generation occurred mostly in the early period of scotophase, while other generations were caught slightly later. Our results contribute to effective pheromone trapping for monitoring and mass trapping to better control G .  pyloalis populations.